2017
DOI: 10.1152/physiolgenomics.00131.2016
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of aging-associated immune system alterations in the rostral ventrolateral medulla of F344 rats

Abstract: The rostral ventrolateral medulla (RVLM) is an area of the brain stem that contains diverse neural substrates that are involved in systems critical for physiological function. There is evidence that aging affects some neural substrates within the RVLM, although age-related changes in RVLM molecular mechanisms are not well established. The goal of the present study was to characterize the transcriptomic profile of the aging RVLM and to test the hypothesis that aging is associated with altered gene expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Furthermore, DAVID ( Huang da et al, 2009 ) functional annotation shows that the majority of the up-regulated genes are associated with the innate and inflammatory immune responses ( Figure 1C ). Interestingly, the immune response-related functions were also found to have significant changes during aging ( High, 2004 ; Weinberger et al, 2008 ; Balivada et al, 2017 ), indicating that immune response-related genes may play important roles during the hippocampal aging process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, DAVID ( Huang da et al, 2009 ) functional annotation shows that the majority of the up-regulated genes are associated with the innate and inflammatory immune responses ( Figure 1C ). Interestingly, the immune response-related functions were also found to have significant changes during aging ( High, 2004 ; Weinberger et al, 2008 ; Balivada et al, 2017 ), indicating that immune response-related genes may play important roles during the hippocampal aging process.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these findings, Sharma [36] observed no age-related changes in brainstem levels of GABA, glycine, and glutamate in non-heated adult rats. On the other hand, Balivada et al [2] reported upregulation of RVLM immune response-associated genes and pathways with advancing age in F344 rats, as well as age-related alterations in genes involved with lipid metabolism and transport, and neurotransmission. These findings suggest that aging may modify the basal expression of genes in the RVLM involved in key molecular pathways and functions, rather than influencing ionotropic receptor transcripts, modifications that may contribute to age-dependent changes in the diverse physiological systems served by this brainstem area.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were divided into two groups, the first group of young (n=10) and aged (n=10) F344 rats was used for gene expression studies, and with second group of young (n=8) and aged (n=8) was used for immunoblotting studies. The brains collected from young and aged rats were subjected to brain sectioning and RVLM micropunching protocols that were performed as described in our previous manuscript [2]. The stereotaxic coordinate system along with its photographic documentation of histologically stained hindbrain sections of the rat brain atlas by Paxinos and Watson [31], were used as references to locate and identify the hindbrain region containing the RVLM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such reasons include the need for investigators to survey the effects of factors that produce global, whole-organism or whole-subdivision effects that are poorly understood at a regional or cellular level. These include environmental agents [257], pharmacological interventions [200], ontogenic state (e.g., see introductory remarks in [27]), or physiological processes. J. Miller et al (2014) [281] examined various hypothalamic sub-regions within the context of a hemispheric tissue analysis in prenatal human brain using high throughput transcriptomic methods.…”
Section: Molecular Mining Of the Hypothalamusmentioning
confidence: 99%